Unilateral Agenesis of the Internal Carotid Artery: A Report of Two Rare Cases - Hadei, Seyed Kamaledin; Ramezani, Mahdi; Taherian, Reza (Galen Medical Journal, 2022)
Background: Internal carotid artery (ICA) agenesis occurs when one or both of the blood vessels that supply blood to the brain do not develop. Congenital agenesis of the ICA rarely occurs. It is usually asymptomatic but may sometimes associate with neurological symptoms such as migraine and pulsatile tinnitus. Moreover, differentiating it from occlusion of ICA is important in patients with stroke. Case Report: We report two cases (63-years-old man and 69-year-old woman) of asymptomatic unilateral ICA agenesis who were referred to our cardiovascular hospital for coronary artery bypass graft. Due to a suspicious history of transient ischemic attack, the patients underwent carotid ultrasonography. With findings suggestive of unilateral ICA agenesis at color Doppler, patients underwent computed tomography angiography that confirmed the diagnosis. Conclusion: Suspecting ICA agenesis at color Doppler imaging of the neck and differentiating it from occluded ICA at CT angiography is important for correct diagnosis and management of the patients.